A theoretical study of the strain-modified RKKY interaction in magnetically doped carbon materials - Gorman, Paul D. (Trinity College (Dublin, Ireland). School of Physics, 2015)
Graphene-related materials continue to be in the scientific limelight due to near-continuous discoveries regarding their properties and production. The applications envisaged for these super materials are numerous and varied across many disciplines. In addition to this, the simplicity with which the physical properties of these materials can be described makes them particularly popular in theoretical examinations, where the simple dispersion relation for their electrons is of key utility. In this thesis we will examine a number of topics relating to graphene systems, focusing on those doped with magnetic impurities. We will utilize a combination of analytical and numerical methods to explore these topics in graphene and carbon nanotubes.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin